Inclusão escolar de crianças com transtorno do espectro autista: um estudo longitudinal - Agripino-Ramos, Cibele Shírley (2019)
Taking the historical-cultural perspective as a theoretical framework, we aim at the relevance of the childhood education’s spaces as facilitators of the development of children with Autistic Spectrum Disorder (ASD). Hence, this research’s main goal was to analyze, during one school year, the social interactions between children with ASD and with typical development (TD), considering the educators’ mediation, as well as their conceptions, and the parents’ and peers’ when it comes to inclusive school for children with ASD, taking place in two Reference Centers in Early Childhood Education (CREI) in the city of João Pessoa-PB. Three children with ASD, aged 4-5 years, nine educators, 42 children with TD, parents of children with ASD and 20 parents of children with TD took part of the study. The CARS evaluation scale was applied, by means of which it was verified that one of the children with ASD had a severe level of the disorder and the other two showed a mild-to-moderate level. Semi-structured interviews with educators, parents and children with TD, at the beginning and end of the school year, were also performed, all of which were analyzed using Bardin's content analysis technique, as well as observations from social interactions in the classroom, in five moments of the year, analyzed as of the identification of interactional episodes. Where results are concerned, the educators described the children with ASD mainly as of their socialization difficulties and behavioral changes, accounting as insufficient the support that they received from CREI in order to work with them and pointing out the internet as the main source of information. However, at the end of the school year, educators from both CREI assumed that they noticed positive changes in the behaviors of children with ASD, which was also reported by the parents of such children, in spite of the concerns revealed by those in relation to their child's entry into an elementary school institution. As for the conceptions of children with TD, terms such as “special” or “baby” were used so as to characterize their classmates with ASD, which seemed to be related to the way that educators referred to children with the disorder. In addition, children with ASD were mentioned by their peers as being among their favorite classmates and, over time, started to be seen by them for their abilities and interests. A fact that must be highlighted is that, as peers with whom children with TD did not play, were cited other children with TD who presented aggressive behaviors, showing a greater degree of rejection to the latter than to their peers with ASD. Parents of children with TD, in turn, said that they were in favor of the inclusion of children with ASD in schools, however, showed no knowledge in relation to the disorder. As for the analysis of the observations, it was found that children with a mild-to-moderate level of the disorder had social interactions for a longer period of time than that with a severe level, moreover, whereas in CREI 1 the interactions between the child with ASD and their peers became more frequent during the year, in CREI 2 the interactions had more participation of educators. Among the contextual aspects considered as favorable to the interactions between children with ASD and the ones with TD, we highlight, besides the encouragement by educators seeking for the participation of children with ASD, the use of objects that aroused interest for children with the disorder. We emphasize the relevance of the outcomes obtained by offering clues about social interactions involving children with ASD and how to promote them in everyday experiences in childhood education, highlighting the interactive possibilities of children with ASD, but also the need to establish strategies that will favor both the conceptions and the interactions in the context of childhood education.